Teknologi Finansial, Literasi Keuangan, dan Keputusan Investasi Produk Reksa Dana di Indonesia - Kusumahadi, Teresia Angelia; Utami, Novia (Universitas Kristen Maranatha, 2022)
The study aims to examine the characteristics of mutual fund financial technology users, the relationship between the use of investment financial technology and financial literacy on investment decisions, and differences in financial literacy between investors who use financial technology and investors who do not. Using a sample of 219 respondents who had or currently have mutual fund investment products in Indonesia, the authors find that most respondents have used financial technology, with Bibit and Bareksa as the most frequently used platforms. Using the OLS method, financial literacy positively and significantly affects investment decisions. On the other hand, the use of financial technology does not impact investment decisions. In addition, investors who use financial technology services have lower financial literacy scores than investors who do not use financial technology. This finding emphasizes the need for more equitable education of financial technology and financial literacy, which is expected to increase financial inclusion.